2014
DOI: 10.1007/s40477-014-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of color Doppler ultrasound in the evaluation of renal transplantation from living donors

Abstract: Purpose The aim of this study was to evaluate the same kidney before and after transplantation to assess the ability of the allograft to restore blood flow, time required to achieve functional recovery after surgery and the possibility of differentiating normal from pathological allografts using color Doppler ultrasound (CDUS) flow indices: resistive index (RI)/renal cortical ratio (RCR) and scintigraphy. Materials and methods 79 living donors and 79 recipients. Donors underwent renal CDUS and scintigraphy. CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…However, we have found correlation between RI value and graft function during the early period after transplantation. So, this study shows that although there is no correlation between RI values and both near and long‐term graft function, the value of RI is a useful parameter in monitoring graft function early after renal transplantation . In addition, we found that the rate of recovery of graft function had correlation with RI early after transplantation and we also found that the rate of recovery of graft function was correlated with both the graft function at first year and also with GFR at first year and last visit of patients.…”
Section: Discussionmentioning
confidence: 47%
“…However, we have found correlation between RI value and graft function during the early period after transplantation. So, this study shows that although there is no correlation between RI values and both near and long‐term graft function, the value of RI is a useful parameter in monitoring graft function early after renal transplantation . In addition, we found that the rate of recovery of graft function had correlation with RI early after transplantation and we also found that the rate of recovery of graft function was correlated with both the graft function at first year and also with GFR at first year and last visit of patients.…”
Section: Discussionmentioning
confidence: 47%
“…In these patients, postoperative bedside Doppler ultrasonography is recom mended. 14 The most common causes of renal artery thrombosis are technical complications, including faulty suture techniques producing incomplete intimal reapproximation with secondary intra luminal fibrosis.…”
Section: Renal Artery Thrombosismentioning
confidence: 99%
“…However, in cases where this is not successful, we have resorted to surgical reconstruction. [12][13][14][17][18][19][20][21] Transplant renal artery stenosis (TRAS) is a relatively frequent, potentially curable cause of refractory hypertension and allograft dysfunction that accounts for approximately 1% to 5% of cases of post transplant hypertension (renal transplant arterial stenosis). In some series, the incidence of TRAS was reported to be 25%.…”
Section: Renal Artery Stenosismentioning
confidence: 99%
“…Postoperative RI evaluation confirmed good allograft status after 24 hours from transplantation (15) and a lower RI after 1 week was associated with satisfying graft function at 6 months (16). Conversely, RI>0.8 after 3, 12 and 24 months was associated with higher mortality, but not with an increased need for dialysis or renal-allograft histological features (17).…”
mentioning
confidence: 94%